ANOTHER ALTERNATIVE IN TEACHING ENGLISH: A Theoretical Perspective - Abd. Ghofur (IAIN MADURA, 2013)
The objective of this written, actually, going to show that literature is a good way to deliver a language learning, in this case leaners could comprehend the language itself by literature as medias of teaching. In this case, of one the literature that could use as a technique to teach language, especially English is drama. Drama can foster skills such as reading, writing, speaking and listening by creating a suitable context. Drama is a powerfull language teaching tool that involves all of the students interactively all of the class period. Drama can also provide the means for connecting students’ emotions and cognition as it enables students to take risk with language and experience the connection between thought and action. Teaching English as a foreign language inevitably involves a balance between receptive and productive skills; here drama can effectively deal with this requirement. Through drama, a class will address, practice and integrate reading, writing, speaking and listening. Drama also fosters and maintains students’ motivation, by providing an atmosphere which is full of fun and entertainment. In so doing, it engages feelings and attention and enriches the learners' experience of the language.